2021
DOI: 10.1001/jamahealthforum.2021.3177
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Medicaid Spending and Use of Drugs With US Food and Drug Administration Accelerated Approval

Abstract: IMPORTANCEState Medicaid programs have reported concerns about rising drug prices and spending, particularly regarding drugs entering the market through the accelerated approval program under the US Food and Drug Administration (FDA). The accelerated approval program enables the FDA to approve drugs on the basis of unverified surrogate end points, meaning that clinical benefits for these products are uncertain at the time of approval. However, state Medicaid programs are legally required to cover these drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The accelerated approval program has evolved substantially since its establishment. A previous study 6 found that, in the pathway's first decade, only 40 approvals were granted for HIV/AIDS medications (40%), oncologic products (30%), and other conditions (30%). Since then, the program has changed in 2 key ways.…”
Section: Changes Over Timementioning
confidence: 99%
See 3 more Smart Citations
“…The accelerated approval program has evolved substantially since its establishment. A previous study 6 found that, in the pathway's first decade, only 40 approvals were granted for HIV/AIDS medications (40%), oncologic products (30%), and other conditions (30%). Since then, the program has changed in 2 key ways.…”
Section: Changes Over Timementioning
confidence: 99%
“…Between 2011 and 2020, this number increased to 12.9 approvals per year. 6 Second, the conditions for which manufacturers seek accelerated approval have also changed, shifting toward oncologic products. In 2020, 28 of the 30 approvals made were for products with oncologic indications, most of which were highly focused (eg, treatment must be for refractory illness or after previous specific courses of treatment).…”
Section: Changes Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…This approach reduces revenues for highly effective drugs such as imatinib (Gleevec), which received accelerated approval in 2001, while still allowing enormous expenditures on minimally effective drugs such as eteplirsen (Exondys 51), which received accelerated approval in 2016 and was listed at $300 000 per year. Even for drugs eventually showing no benefit of any amount-Sachs et al 1 The conflation of evidence with efficacy also diverts attention from the far larger volume of drugs without accelerated approval that contribute to high Medicaid drug expenditures. 1 New drugs, with or without accelerated approval, tend to represent a disproportionate share of total pharmaceutical expenditures.…”
mentioning
confidence: 99%